Effects of Program for Couple Counseling Based on Islamic Principles on Intention Using Norplant for Birth Spacing among Muslim Teenage Postpartum Mothers - Su, Nureema; Youngwanichsetha, Sununta; Chatchawet, Warangkana (Princess of Naradhiwas University Journal, 2021)
The purpose of this quasi-experimental research was to study the effects of program for couple counseling based on Islamic principles on intention to use Norplant for birth spacing among Muslim teenage postpartum mothers who admitted to the postpartum units of a general hospital, Thailand. Twenty-five Muslim teenage postpartum mothers were selected by criterion and assigned into each of the experimental and control group. The experimental group provided the program for couple counseling based on Islamic principles, while the control group imported a routine care. The research instruments comprised of 2 parts: (1) questionnaires including the general information, the Birth Spacing of Muslim Teenage Postpartum Mothers and the Husband’s Personal Information Questionnaire and (2) the Scale of intention to Use Implants for Birth Spacing. All instruments in this study were content validated by three experts. The reliability of the Scale of intention to Use Implants for Birth Spacing was examined using Cronbach’s alpha coefficient, yielding a value of .81. The data were analyzed using frequency, percentage, mean, standard deviation, chi-square, Likelihood ratio, Fisher’s exact test and independent t-test. The hypotheses were tested using independent t-test and paired t-test. The results showed that: (1) subjects in the experimental group had significantly higher mean score of intention to use implants for birth spacing after intervention than before intervention (t = 23.53, p<.001); and (2) subjects in the experimental group had significantly higher mean score of intention to use implants for birth spacing after intervention than of subjects in the control group (t = 17.84, p<.001). The results showed that the program for couple counseling based on Islamic principles could help Muslim teenage postpartum mothers increase their intention to use implants for birth spacing. Therefore, the program should be utilized to promote a birth spacing, especially in Muslim context.